Towards understanding language organisation in the brain using fMRI. - Matthews, P; Adcock, J; Chen, Y; Fu, S; Devlin, J; Rushworth, M; Smith, S; Beckmann, C; Iversen, S (2003)
Functional magnetic resonance imaging (fMRI), which allows non-invasive mapping of human cognitive functions, has become an important tool for understanding language function. An understanding of component processes and sources of noise in the images is contributing to increased confidence in the reproductability of studies. This allows clinical applications, e.g., for pre-surgical lateralisation of language functions in patients with temporal lobe epilepsy. fMRI is a sensitive method for mapping regions involved in language functions. We recently have applied it to study the effect of word surface form on reading with a comparison of responses to Chinese characters or alphabetical Pinyin. Interpretation of fMRI activations must be made with caution; fMRI suggests task-associated activation, but does not independently confirm that such activity is necessary. However, complementary studies can be performed using transcranial magnetic stimulation (TMS), which can be used to interfere with brain activity in a specific region transiently for characterisation of the behavioural effects. We describe how TMS combined with fMRI has confirmed a role for the left inferior frontal cortex in semantic processing.